Challenges, barriers, and determinants of farmers’ adoption of agroecological practices in Tunisia: A Case study of Hamam biadha and Elles - Khader, Amina (2024)
Agriculture in Tunisia is associated with unsustainable farm practices in an environment highly vulnerable to climate change, along with a general lack of political support. Agroecology is considered as a potential solution. Therefore, urgent need to investigated Tunisian agricultural environment, and farming practices are required. This study aims to assess the challenges and barriers and to identify key determinants of farmer’s adoption of agroecological practices in Hamam Biadha and Elles area. Data has been collected through interviewing 40 farmers, 16 key informant interviews (KII’s) and 2 focus groups discussions (FGD’s) targeting stakeholders. Based on the data processing, and their findings out, a SWOT analysis was performed. Structured interviews, informed by surveys, delved into farmers' agricultural practices, barriers to adoption, and motivations for embracing agroecological techniques, while open and semi-structured interviews captured stakeholders' perspectives on benefits, barriers, and adoption influencers. In the empirical analysis, qualitative and quantitative approaches were used, including factor and bivariate analysis (i.e., Kendall’s test). Farm typologies, predominantly mixed systems combining cereal-tree-small ruminant components, were identified. Most of the agroecological practices found were traditional: Rotation accounted for the highest percentage (65%), followed by manure (35%), and lastly, biochar (3%). Results reveal that farmers are facing several barriers. Drought emerged as the primary impediment to adoption of agroecological practices (100%), followed by resources access constraints (eg. organic inputs and local seeds) (60%) and market-related factors, such as trails and roads (25%). Future initiatives should prioritize cooperative support to facilitate the transition toward agroecological practices, and bolstering food system resilience. The study concludes that the adoption of agroecological practices has economic, political, social, and institutional components. To enhance the adoption of such practices, empirical findings suggest the need for greater investment (capacity building, incentives, building farmer’s organizations, etc.) to remove these barriers and institutional shortcomings. In addition. Further research is required in order to understand farmers’ needs, social dynamics, and perceptions, vital components for establishing better farmer organizations, considered as accelerator and facilitator for wider adoption of agro-ecological practices.